Effect of Methylobacterium extorquens on tomato development in the presence or absence of Fusarium oxysporum - Medina-Rios, Melissa; Ceja Torres, Luis Fernando; López-Díaz, Sigifredo; Venegas-González, José; Sánchez-Hernández, Carla Vanessa (Revista Mexicana de Ciencias Agrícolas, 2019)
The wilting of tomato (Fusarium oxysporum) promotes the excessive use of synthetic fungicides, which are not economically or environmentally viable. This work proposes the use of Methylobacterium extorquens to determine its effect on plant development and the signaling pathway, for the defense of tomato plants, against phytopathogens. From tomato seeds var. SUN 7705 embedded and plants sprinkled with the bacteria at a concentration of 109 CFU mL-1, were challenged to the plant with the fungus in two tests. Variables of root length in seedlings, plant height, leaf amplitude, yield, total dry weight of the plant and dry root weight were measured. A completely randomized design with six treatments and four repetitions was used, two plants formed the experimental unit. Likewise, an essay was carried out on the expression of defense genes, in tomato seedlings of the same variety. Significant statistical differences (p≤ 0.05) were found between treatments embedded and sprinkled with M. extorquens and the treatments inoculated with F. oxysporum and the controls, reflecting in the seedling root length, plant height, leaf amplitude, dry weight of the plant and the root, as well as in the yield. However, the genes encoding the phenylalanine ammonium lyase (PAL), protein (PR-6), superoxide dismutase (SOD) and lipoxygenase (LOX) enzyme group, were not significantly expressed in seedlings treated with M. extorquens.
Keywords: Fusarium; Methylobacterium extorquens; Solanum lycopersicum; Oxysporum; biological control